Wild pollinators enhance oilseed rape yield in small-holder farming systems in China - Zou, Yi; Xiao, Haijun; Bianchi, Felix J. J. A.; Jauker, Frank; Luo, Shudong; van der Werf, Wopke (BMC ecology, 2017)
Insect pollinators play an important role in crop pollination, but the relative contribution of wild pollinators and honey bees to pollination is currently under debate. There is virtually no information available on the strength of pollination services and the identity of pollination service providers from Asian smallholder farming systems, where fields are small, and variation among fields is high. We established 18 winter oilseed rape (Brassica napus L.) fields along a large geographical gradient in Jiangxi province in China. In each field, oilseed rape plants were grown in closed cages that excluded pollinators and open cages that allowed pollinator access. The pollinator community was sampled by pan traps for the entire oilseed rape blooming period. Oilseed rape plants from which insect pollinators were excluded had on average 38% lower seed set, 17% lower fruit set and 12% lower yield per plant, but the seeds were 17% heavier, and the caged plants had 28% more flowers and 18% higher aboveground vegetative biomass than plants with pollinator access. Oilseed rape plants thus compensate for pollination deficit by producing heavier seeds and more flowers. Regression analysis indicated that local abundance and diversity of wild pollinators were positively associated with seed set and yield/straw ratio, while honey bee abundance was not related to yield parameters. Wild pollinator abundance and diversity contribute to oilseed rape yield by enhancing plant resource allocation to seeds rather than to above-ground biomass. This study highlights the importance of the conservation of wild pollinators to support oilseed rape production in small-holder farming systems in China.